THE INFLUENCE OF FINANCIAL PERFORMANCE, COMPANY SIZE AND GOOD CORPORATE GOVERNANCE ON SUSTAINABILITY REPORT DISCLOSURE IN MANUFACTURING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Wahyuddin; Yanita; Cike Sifa Kinanti (Universitas Efarina, 2024)
This research aims to analyze the influence of Financial Performance, Company Size, and Good Corporate Governance on the disclosure of Sustainability Reports in manufacturing companies listed on the Indonesia Stock Exchange. The population in this study was 226 manufacturing companies using purposive sampling techniques, so that a sample of 18 companies was obtained and had 90 observations. The estimation model for this research uses panel data regression with Random Effect Model (REM) using Eviews software. This research uses secondary data obtained from financial reports and can be accessed via www.idx.co.id. The results of this research found that Financial Performance with profitability ratios (ROA) had a positive and insignificant influence on sustainability reports, Company Size (SIZE) had a positive and insignificant influence on sustainability reports and Good Corporate Governance had a positive and significant influence on sustainability reports.